Application of AquaCrop model in deficit irrigation management of winter wheat in arid region - Salemi, Hamidreza; Mohd Soom, Mohd Amin; Lee, Teang Shui; Mousavi, Sayed Farhad; Ganji, Arman; Yusoff, Mohd Kamil (Academic Journals, 2011)
Simulation models that clarify the effects of water on crop yield, are useful tools for improving farm-level water management and optimizing water use efficiency. The main purpose of deficit irrigation is high water productivity with less water supply to plants. In this research, the potential of AquaCrop model in deficit irrigation practice for winter wheat, the main agronomic crop in Gavkhuni river basin, Isfahan province, Iran, was studied. The results of reliability indices such as RMSE, d, E, CRM and deviation percent were 2.31 to 5.63, 0.97 to 1.00, 93 to 99, -0.15 to 0.016 and -0.70 to 12.00% respectively, and showed that, the model overestimated the simulated parameters compared with field data. This difference was more obvious in deficit irrigation treatments. The model provided excellent simulations of canopy cover, grain yield and water productivity. Considering only drought stress and neglecting other stresses such as salinity is the most important limitation of AquaCrop model. In this study, water productivity for the studied crop was in the range of 0.91 to 1.49 kg m-3 and its maximum value was in 40% deficit irrigation treatment. Asecond-order, yield-water function, obtained in this study is recommended for winter wheat crop. Also, the sensitivity analysis of AquaCrop model was carried out for winter wheat in this arid area in central Iran.